Effect of repetitive transcranial magnetic stimulation on upper limb motor function in stroke patients with right hemiplegia based on EEG microstates and EMG - Yu, Xianxian; Xin, Rong; Cheng, Siman; Xie, Jiale; Ling, Gengqiang; Wei, Xin; Wang, Pu (Frontiers in Neurology, 2025)
IntroductionStroke severely impairs neural function and daily living, creating an urgent need for innovative rehabilitation strategies. This study aimed to investigate the effects of transcranial magnetic stimulation (TMS) on upper limb motor recovery in stroke patients, combining EEG microstate analysis and EMG to elucidate associated neuromuscular and cortical changes.MethodsTwenty patients with right-hemiplegic stroke and twenty healthy controls were enrolled. Patients underwent Fugl-Meyer Assessment for Upper Extremity (FMA-UE) and Action Research Arm Test (ARAT) before and after repetitive TMS (rTMS) intervention. Resting-state EEG and EMG recordings were acquired pre- and post-one week of rTMS treatment.ResultsFollowing rTMS, patients exhibited significant improvements in FMA-UE and ARAT scores (p < 0.05). EEG microstate analysis indicated that stroke patients initially showed decreased time coverage and occurrence of Microstate B (associated with sensorimotor integration, p < 0.05). After rTMS, these parameters increased markedly, approaching levels observed in healthy controls (p < 0.05). In contrast, Microstate C (motor execution-related) and Microstate D (attention-related) displayed reduced duration and coverage post-intervention (p < 0.05). Critically, enhancement in Microstate B metrics correlated with improved motor coordination in specific muscles (flexor/extensor carpi ulnaris, p < 0.05), while changes in Microstate C were positively correlated with gains in upper limb strength.DiscussionThese findings highlight two central mechanisms: (1) rTMS promotes motor recovery in hemiplegic patients by normalizing cortical dynamics, as reflected in microstate reorganization; (2) Microstate B and C represent promising neurophysiological biomarkers for tracking rehabilitation progress, with the former reflecting motor coordination and the latter indexing strength recovery. This study bridges microstate-level neurophysiological changes and functional improvements, supporting rTMS as a precision intervention in stroke neurorehabilitation. Further research should validate these biomarkers in larger cohorts and explore microstate-guided rTMS protocols.Clinical trial registrationchictr.org.cn, Identifier: ChiCTR2100049509.